2023
DOI: 10.24310/innoeduca.2023.v9i1.15286
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between technological change, digitization, and students’ attitudes toward distance learning in Lagos Higher Education institutes

Joy Onyekwere,
Kazi Enamul Hoquei

Abstract: The focus of this research is to investigate the relationship between learning flexibility, support services, and students' attitudes toward remote learning programs in Nigeria. A correlational research methodology is used, and 385 individuals drawn from a multi-stage sampling technique form the study's sample. The data collecting tool is a three-section questionnaire devised by the researchers. Experts validated the questionnaire, which was then administered once on a randomly selected sample to assess the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They found it difficult to manage their time for online classes, assignments, study time and entertainment. Contradicting this, there is a positive relationship between digitised content in a distance-learning programme (Onyekwere, & Hoque, 2023). Additionally, the results pointed out that due to usage of OTT, students were not able to manage time in such a way that allowed them to develop skills, pursue hobbies and socialise with friends.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 97%
“…They found it difficult to manage their time for online classes, assignments, study time and entertainment. Contradicting this, there is a positive relationship between digitised content in a distance-learning programme (Onyekwere, & Hoque, 2023). Additionally, the results pointed out that due to usage of OTT, students were not able to manage time in such a way that allowed them to develop skills, pursue hobbies and socialise with friends.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 97%
“…The research model is based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). Similar research models have been successfully applied in various contexts, such as examining students' initial perceptions of QR codes (Abdul Rabu et al, 2018), analyzing the intentions of future teachers to use Web 2.0 technologies in their courses (Şimşek, & Ateş, 2022), exploring students' attitudes towards distance learning programs (Onyekwere, & Enamul Hoque, 2023), and investigating students' behavior regarding the adoption of cloudbased virtual platforms (Sayginer, 2023). The current study identified social influence, facilitating conditions, hedonic motivation, perceived usefulness, and perceived ease of use as significant factors influencing students' acceptance of QR code usage in the Organic Chemistry course.…”
Section: Coefficient Of Determination (R 2 )mentioning
confidence: 99%
“…This transition has revolutionized the educational sphere, placing learning resources directly at students' fingertips, and effectively dissolving the traditional constraints of geography and time. Such a transformation necessitates learning methodologies that are not only flexible and adaptable but also aligned with the dynamic digital context (Alenezi, 2023;Onyekwere, & Enamul Hoque, 2023).…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%